Maternally Inherited Diabetes Mellitus Associated with a Novel m.15897G>A Mutation in Mitochondrial tRNAThr Gene - Ke Li; Lijun Wu; Jianjiang Liu; Wei Lin; Qiang Qi; Tianlan Zhao (Journal of Diabetes Research)
We report here the clinical, genetic, and molecular characteristics of type 2 diabetes in a Chinese family. There are differences in the severity and age of onset in diabetes among these families. By molecular analysis of the complete mitochondrial genome in this family, we identified the homoplasmic m.15897G>A mutation underwent sequence analysis of whole mitochondrial DNA genome, which localized at conventional position ten of tRNAThr, and distinct sets of mtDNA polymorphisms belonging to haplogroup D4b1. This mutation has been implicated to be important for tRNA identity and stability. Using cybrid cell models, the decreased efficiency of mitochondrial tRNAThr levels caused by the m.15897G>A mutation results in respiratory deficiency, protein synthesis and assembly, mitochondrial ATP synthesis, and mitochondrial membrane potential. These mitochondrial dysfunctions caused an increase in the production of reactive oxygen species in the mutant cell lines. These data provide a direct evidence that a novel tRNA mutation was associated with T2DM. Thus, our findings provide a new insight into the understanding of pathophysiology of maternally inherited diabetes.